Human health benefits from livestock vaccination for brucellosis: case study - Roth Felix; Zinsstag Jakob; Orkhon Dontor; Chimed-Ochir G.; Hutton Guy; Cosivi Ottorino; Carrin Guy; Otte Joachim (The World Health Organization, 2003)
OBJECTIVE: To estimate the economic benefit, cost-effectiveness, and distribution of benefit of improving human health in Mongolia through the control of brucellosis by mass vaccination of livestock. METHODS: Cost-effectiveness and economic benefit for human society and the agricultural sector of mass vaccination against brucellosis was modelled. The intervention consisted of a planned 10-year livestock mass vaccination campaign using Rev-1 livestock vaccine for small ruminants and S19 livestock vaccine for cattle. Cost-effectiveness, expressed as cost per disability-adjusted life year (DALY) averted, was the primary outcome. FINDINGS: In a scenario of 52% reduction of brucellosis transmission between animals achieved by mass vaccination, a total of 49 027 DALYs could be averted. Estimated intervention costs were US$ 8.3 million, and the overall benefit was US$ 26.6 million. This results in a net present value of US$ 18.3 million and an average benefit-cost ratio for society of 3.2 (2.27-4.37). If the costs of the intervention were shared between the sectors in proportion to the benefit to each, the public health sector would contribute 11%, which gives a cost-effectiveness of US$ 19.1 per DALY averted (95% confidence interval 5.3-486.8). If private economic gain because of improved human health was included, the health sector should contribute 42% to the intervention costs and the cost-effectiveness would decrease to US$ 71.4 per DALY averted. CONCLUSION: If the costs of vaccination of livestock against brucellosis were allocated to all sectors in proportion to the benefits, the intervention might be profitable and cost effective for the agricultural and health sectors.